Simultaneous Determination of Amlodipine and Ramipril by High Performance Thin Layer Chromatography - GUPTA, K.R.; WANKHEDE, S.B.; TAJNE, M.R.; WADODKAR, S.G. (Asian Journal of Chemistry, 2010)
A simple, selective and validated high performance thin layer chromatographic method has been developed for the simultaneous estimation of amlodipine and ramipril in tablets. Aluminium plates precoated with silica gel G 60 F254 was used as stationary phase and toluene:ethanol:acetone: ammonia in the ratio of (7:2:1:0.3 v/v) was used as mobile phase. Quantification was carried out by the use of densitometric absorbance mode at 217 nm. The content of amlodipine and ramipril in tablet/capsule formulation was calculated and found to be 98.66/99.25, 100.17/99.36, 99.93/100.39 and 99.96/100.06 % by height and area for tablet and capsule, respectively. The proposed HPTLC method was quantitatively evaluated in terms of stability, precision, repeatability, accuracy and calibration correlation proving its utility in routine analysis of its tablet dosage form.